2004
DOI: 10.1584/jpestics.29.364
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Neonicotinoids of Chicken .ALPHA.7 Nicotinic Acetylcholine Receptors: Effects of Mutations of Isoleucine 191 in Loop F to Aromatic Residues

Abstract: The effects on the responses to neonicotinoids and related nicotinic agonists of three site-directed mutations (I191W, I191F and I191Y) in loop F of the acetylcholine-binding site were studied using the chicken a7 nicotinic acetylcholine receptor (nAChR) expressed in Xenopus laevis oocytes. Voltage-clamp electrophysiology was employed to show that, whereas the I191F mutation scarcely affected the concentration-response curves for neonicotinoids, the I191W mutation increased the maximum amplitude of responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In loop F of insect non‐α subunits, aromatic residues are present at the position corresponding to isoleucine (Ile) 191 of the chicken α7 subunit, and tryptophan (Trp) residues are most frequently observed. Based on mutagenesis studies on the α7 receptor, it is assumed that a Trp residue in loop F may contribute to strengthening the n AChR–insecticide interaction as well 69…”
Section: Neonicotinoid Bindingmentioning
confidence: 99%
“…In loop F of insect non‐α subunits, aromatic residues are present at the position corresponding to isoleucine (Ile) 191 of the chicken α7 subunit, and tryptophan (Trp) residues are most frequently observed. Based on mutagenesis studies on the α7 receptor, it is assumed that a Trp residue in loop F may contribute to strengthening the n AChR–insecticide interaction as well 69…”
Section: Neonicotinoid Bindingmentioning
confidence: 99%
“…As non-α subunits lack the necessary loop C sequences, they cannot form homopentamers and only create binding sites when adjacent to α subunits with necessary loop sequences. Electrophysiological analyses and structural studies have identified residues in loop sequences critical to nAChR–imidacloprid responses. Characterizing the expression of residues across all nAChR subunits is needed to predict functionality and, by extension, DSS.…”
Section: Resultsmentioning
confidence: 99%
“…Imidacloprid causes dysfunction by acting as a partial agonist of the nicotinic acetylcholine receptor (nAChR) . Given that considerable electrophysiological and structural analyses have already identified specific loop sequences and residues critical to nAChR–imidacloprid binding, nAChRs should be particularly amenable to a toxicogenomic predictive approach. Indeed, residue changes identified using electrophysiology that reduce nAChR responses to imidacloprid have been associated with lower imidacloprid sensitivity in ticks and aphids. , Therefore, applying a predictive toxicogenomic approach to nAChRs that accounts for amino acid identity and expression in loop residues critical to LBD–imidacloprid interactions has great potential to improve neonicotinoid sensitivity predictions.…”
Section: Introductionmentioning
confidence: 99%